Evaluasi Keamanan Tempe dari Kedelai Transgenik Melalui Uji Subkronis pada Tikus (SAFETY EVALUATION OF TEMPE MADE FROM TRANSGENIC SOYBEAN USING SUBCHRONIC TEST ON RATS) - Suwarno, Maryani; Astawan, Made; Wresdiyati, Tutik; Widowati, Sri; Bintari, Siti Harnina; ., Mursyid (Jurnal Veteriner, 2014)
The consumption need of soybean that reached up to 2,5-3 million tons per year has made Indonesiaimports this commodity 1,95 million tons from countries that adopt Genetically Modified (GM) soybean.Soybean utilization for tempe producers is about 50% from total its supply. The aim of this research wasto evaluate the safety of tempe made from GM soybean, by a subchronic test approach using male Sprague-Dawley rats. Toxicity evaluation of tempe from soybean GM was done based on EFSA (2011) principalusing animal laboratory. For 90 days, three groups of male rats (each group contain seven rats) werefeeding with tempe flour from GM soybean, tempe flour from non-GM soybean and control group wasfeeding with casein as a protein source. All rats were terminated on day 90,where the blood, liver andkidney were collected. There were no significant differences on liver and kidney weight between treatment.Hematology analysis showed the level of Hb, erythrocyte, leucocyte, trombocyte and hematocryte were notsignificantly different in between group. Serum analysis on SGOT, SGPT, total protein, albumin, globulin,blood glucose, triglyceride, ureum and creatinin level were also showed no difference between groups. As aconclusion, the consumption of tempe derived from GM soybean was safe, and cause no adverse effect onhealth.
Keywords: soybean, tempe, transgenic, GM, rats, safety